PENINGKATAN PENJUALAN MELALUI PENDAMPINGAN PEMASARAN ONLINE DAN PENGEMBANGAN KEMASAN PRODUK ULAT HONGKONG (TENEBRIO MOLITOR) DI DESA CIHIDEUNG PARONGPONG KAB. BANDUNG BARAT - Kurniawati, Susanti; Sulaeman, Ardika (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2020)
The application of e-marketing and packaging development for mealworms (Tenebrio Molitor) in service partners' business is motivated by the problem of the inability of breeders to meet market demand due to the lack of a wide spread of product marketing networks. Based on this, this community service activity aims to increase breeders’ knowledge, motivation and technical skills to develop online marketing and product packaging and expand the marketing network through online product sales and better packaging. The implementation of this activity is carried out with individual breeder partners for 3 months through the functional participation method by providing direct assistance with interviews, observations, and discussions with partners regarding the problems and solutions applied. The result of this activity is an increase in knowledge, motivation and technical ability of e-marketing as well as the promotion of mealworm products online, informative, illustrative product packaging, able to protect product quality and provide a good image of feed quality. The expansion of marketing and product packaging is able to increase sales of partner products.